Writing the future of biogeography - Brian McGill; Miguel Araújo; Janet Franklin; H. Peter Linder; Michael N Dawson (Frontiers of Biogeography, 2018)
Scientific publishing has seen many changes in its ~350 years of existence. Nonetheless, the changes currently underway may be among the most radical. The five major biogeography journals (Diversity and Distributions, Ecography, Frontiers of Biogeography, Global Ecology and Biogeography, and Journal of Biogeography) are indicative of the major undercurrents in publishing today: two are society owned, three are owned by a private publisher; two are open access, three are reader-pays; four are published by a for‐profit publisher, one is not; three are double-blind review, two are the traditional single blind. Despite these differences, we serve as editors-in-chief for these journals for one common reason: to make sure there is a healthy publishing ecosystem available to communicate biogeographical research. With that goal in mind, here, we provide a brief potted history of scientific publishing to contextualize the modern publishing environment. We consider what current trends may mean for the future of scientific publishing. And we highlight a suite of factors that we recommend be considered when choosing a venue in which to publish your research. We particularly wish to emphasize one point: while editors-in-chief may guide journals, and editors and reviewers shape the science that is published, all journals depend ultimately on the manuscripts that authors choose to submit. For this reason, authors have great power over the future of the publishing landscape. To ensure a healthy landscape, we feel it is critical that all authors—but especially we senior and mid-career authors—are educated about today’s complex world of publication and make informed choices about where to submit, which signals to publishers the criteria that our community values. Authors’ choices now have potential to shape a sustainable publishing environment that better serves current and future generations of biogeographers.